Corporate lawyers and corporate governance - Loughrey, Joan , 1968- (Cambridge ; New York : Cambridge University Press, 2011)
"The role of corporate lawyers and their firms: the issues In 2010 a leading City law firm, Linklaters, attracted unwelcome media attention1 when the bankruptcy examiner?s report into the collapse of Lehman Brothers found that a legal opinion it had provided to its client had been used to mislead US authorities, although there was no suggestion that Linklaters itself had done anything wrong.2 The media interest was short-lived and gave rise to no broader debate about the role corporate law firms played for their corporate clients. In contrast, in the United States, even before Enron collapsed in 2000, there was lively debate on the subject of corporate lawyers and their corporate governance role"-- Provided by publisher
"This assessment of the corporate governance role of corporate lawyers in the UK analyses the extent to which lawyers can and should act as gate-keepers, counsellors and reputational intermediaries. Focusing on external and in-house lawyers? roles in both dispersed share-ownership and owner-managed companies, Joan Loughrey highlights the conflicts of interest that are endemic in corporate representation and examines how lawyers should respond when corporate agents provide instructions contrary to the company client?s interests. She also considers the legitimacy of ?creative compliance?, the ethical arguments for and against lawyers prioritising the public interest over their clients? interests, and their exposure to liability if they fail to perform a corporate governance role. Finally, she considers whether the reforms to the legal profession will promote the lawyer?s corporate governance role and advances suggestions for reform"-- Provided by publisher
1. Introduction; 2. The international perspective; 3. The roles of the corporate lawyer; 4. Identifying the corporate client; 5. The role of the corporate lawyer in shareholder litigation; 6. The corporate lawyer as director; 7. The regulation of the corporate lawyer; 8. The arguments against reform; 9. Reforming the role of the corporate lawyer; 10. The reform of the legal profession and corporate lawyers; 11. Conclusion
Includes bibliographical references (p. 311-335) and index
Keywords: Corporate governance -- Law and legislation -- Great Britain; Corporate lawyers -- Great Britain; Corporation law -- Great Britain